Influence of chitosan methacrylation on mucoadhesiveness of halloysite-chitosan sustained release nanocomposites - Jauković, Valentina; Krajišnik, Danina; Čalija, Bojan (Archives of Pharmacy, 2022)
Halloysite is a clay mineral which can be used as a nanocontainer for prolonged release of active substances, due to its biocompatibility, tubular structure, positive lumen and negative outer surface charge. However, the use of halloysite is limited by low loading capacity and mucoadhesiveness. To increase pore volume and prolong residence time of a drug, halloysite was treated with acetic acid and functionalized with mucoadhesive polymers, chitosan (a cationic polysaccharide) and methacrylated chitosan (degree of methacrylation 27%). The aim of this study was to evaluate the impact of chitosan methacrylation on mucoadhesiveness of halloysite-chitosan nanocomposites. Binding of both polymers at the halloysite surface was confirmed by zeta potential measurements. Halloysite and halloysite-polymer nanocomposites were mixed with an aqueous porcine mucin dispersion (0.1% m/m). After incubation with mucin during 8 h at room temperature, zeta potentials of halloysite-chitosan (HCN) and halloysite-methacrylated chitosan nanocomposites (HMCN) decreased, from +25.9 to -13.3 mV i.e. from +24.4 to -12.6 mV, respectively. The measured zeta potentials were close to zeta potential for pure mucin (-12.2 mV), indicating their interaction. Mucoadhesive properties were further investigated by measuring ability of HCN and HMCN to adsorb mucin using UV/VIS spectroscopy. HMCN were able to adsorb higher % of mucin (≈82%) compared to HCN (≈72%) and pristine halloysite (≈ 58%) after 8 h of incubation. Modification of halloysite with methacrylated chitosan has shown to be efficient in improving of mucoadhesiveness of halloysite-chitosan nanocomposites, which makes them prospective materials for drug delivery applications.